Metode Pendidikan Dalam Perspektif Al-Zarnuji Pada Kitab Ta’lim Al-Muta’alim - Asnimar, Asnimar; Satria, Rengga; Rahman, Rini (Prodi Pendidikan Keagamaan Islam, 2022)
In the teaching and learning process in schools, teachers of certain subjects experience various kinds of obstacles. The essence of these problems is the occurrence of missed understanding or missed communication between the two parties, which in the end has fatal consequences. The purpose of this research is to explain how Sheikh Al-Zarnuji thinks about the method of education in the book of Al-Muta'alim. This research is literature research that uses a qualitative approach and an analytical approach. The data collection technique used is a documentary technique, and the data analysis uses content analysis. Based on the research conducted, it can be concluded that in teaching Al-Zarnuji uses several methods such as the lecture method, discussion, memorization, and example. Then he also explained that the relationship between a teacher and his students must have a good personality, and guard against doubtful things. Not much to laugh at and talk in pointless things. A teacher to his students must be humble and stay away from arrogant pride.